2019
DOI: 10.12659/msm.914031
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Physical Exercise, and the Prevalence of Sarcopenia in Elderly Residents in Nursing Homes in China

Abstract: Background This study aimed to investigate the factors associated with sarcopenia in elderly residents in three nursing homes in Suzhou City, East China including the association with nutrition and physical exercise. Material/Methods Elderly residents (n=316) from three nursing homes included 112 men and 204 women. The appendicular skeletal muscle index (ASMI), grip strength, and movements were measured to diagnose sarcopenia. The correlation between sarcopenia with age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
1
33
0
3
Order By: Relevance
“…were not recorded. However, these play a key role in the occurrence and development of sarcopenia (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…were not recorded. However, these play a key role in the occurrence and development of sarcopenia (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Multiple epidemiological surveys across different regions between Furthermore, the survey by Zhang et al 46 suggested that the overall prevalence of sarcopenia among 1227 Shanghai residents was 14.3%, whereas the prevalence rates of sarcopenia among men and women were 14.9% and 14.0%, respectively. In their survey, Yang et al 47 illustrated that the prevalence of sarcopenia among senior citizens in Jiangsu Province was 28.8%. Additionally, the survey conducted in Tianjin by Han et al 48 encompassing 1069 senior residents who were over 60 years old suggested that the prevalence rates of sarcopenia among male and female residents were 6.4% and 11.5%, respectively.…”
Section: Re S Pir Atory D Is E a S E Smentioning
confidence: 99%
“…MUAC and CC were measured to the nearest 0.1 cm with a non-elastic tape (Deli, China) without compressing the subcutaneous tissue. MUAC was measured at the mid-point around the arm between the acromion and the ulnar olecranon, with the patient's upper limb in a state of natural hanging [35]. CC was measured around the widest part of the calf, while subjects stood with their legs shoulder-width apart [35].…”
Section: Mid-upper Arm Circumference (Muac) and Calf Circumference (Cc)mentioning
confidence: 99%